BUILDING LINK-MATCH OF GEN Z AND THE WORLD OF WORK THROUGH CONTEXTUAL-ADAPTIVE FACILITATION - Januari Ayu Fridayani; Stephanus Eri Kusuma; Albertus Yudi Yuniarto (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2022)
Organizations, both formal and non-formal, that have direct contact with young people have not fully focused on providing facilities that support these young people, especially GenZ, in entering the world of work. This study aims to analyze Generation Z (Gen Z) and employer representatives’ view on current and future work field. Utilizing focus group discussion (FGD) and webinar involving GenZ and employer representatives, we collect data from GenZ and firms representatives. The data is analyzed using descriptive methods. This study identifies some expectation of GenZ related to work field and their thoughts to anticipate the work field needs. Meanwhile, this study also describes the employers’ hope that Gen Z should have some information related to the competitive and other contextual condition condition of workfield and be equipped with some skills to cope with the work field condition. The result of the study asks for the existence of organization that is taking the role as the relevant skill-knowledge provider and advisor to the GenZ before they enter work field. Regarding this, we recommend the existence of organizations that work directly with youth and provide: (1) character education, (2) training with business practitioner to improve soft skills, especially in terms of personal branding, teamwork and building networking, and (3) learning curriculum that gives more portion on practice.